DEFERRED TAX AND ITS IMPACT ON THE MEASUREMENT OF ECONOMIC VALUE ADDED (EVA) - Morales, María Gabriela Morales; Paredes, Paulina Viviana Quinaluisa; Valdez, Juan Gabriel Villagómez; Lafuente, Carlos Alfonso Ramírez (Veredas do Direito, 2025)
Many companies use the concept of Economic Value Added (EVA) as an indicator to evaluate the value generated for their shareholders, implying the need to adjust this metric. This adjustment seeks to convert the book value to economic value, avoiding distortions in the information provided. In the field of Ecuadorian small businesses, this study aims to determine if the deferral of deferred taxes impacts the EVA. The use of quantitative approaches is highlighted, and secondary data was used covering various commercial activities in Ecuador between 2016 and 2019. Adjusted and unadjusted Economic Value Added are compared to analyze the pre- and post-effects of the deferred tax on the relevant variables. The results indicate that the deferred tax can underestimate or overestimate the value of the EVA during the analyzed period. The regression analysis using SPSS reveals the joint relevance of all the predictors of the deferred tax, evidencing its significant impact on the value of the EVA. Consequently, the study suggests that companies make deferred tax adjustments in the calculation of Economic Value Added.